Conceptual Design and Analysis of Small-Scale Wind Turbine for Household Usage in Malaysia - Ruzi, Nor Afifah; Rosly, Nur Hayati (Progress in Aerospace and Aviation Technology, 2023)
Wind energy is a valuable renewable resource that holds great potential for generating electrical power through wind turbines. However, there is a lack of practical and cost-effective small-scale wind turbines designed specifically for household usage. This study aims to address this need by focusing on the design and performance analysis of a small-scale vertical Darrieus wind turbine tailored for household applications in Malaysia. The objective is to propose an optimized turbine design that maximizes energy conversion efficiency. Computational Fluid Dynamics (CFD) simulations using ANSYS Fluent software are conducted to evaluate the turbine's performance, with the power coefficient (Cp) calculated at various tip speed ratios (TSR). Two 3D designs with different blade configurations are developed using SolidWorks for the CFD simulations. The findings from this study contribute to the design optimization and performance evaluation of vertical Darrieus wind turbines, providing a sustainable and viable alternative for residential energy needs. This research addresses the pressing demand for clean and affordable energy solutions in Malaysia and supports the transition towards renewable sources.